Poéticas del archivo: el “giro documental” en la narrativa rioplatense reciente - Paula Klein (Cuadernos LIRICO, 2019)
Río de la Plata’s contemporary literature bears witness to what literary critic Mark Nash refers to as a “documentary turn”. In addition to the incorporation of documentary materials into their texts, the works we designate here as “documentary writings” employ research methods such as the notation, transcription and montage of documents or the citation of an elaborated bibliography. This article aims to articulate a theoretical consideration and a literary study of Argentinian writer and journalist Marta Dillon’s Aparecida (2015), a case representative for the understanding of this documentary device’s mechanics.